Duration of ciprofloxacin use is important in the development of abdominal aortic aneurysm in a rat model - ÖZYILMAZ YAY, NAGEHAN; ERGELEN, RABİA; AKAKIN, DİLEK; GÜLHAN, REZZAN (My University, 2022)
BACKGROUND: Recent findings suggest that fluoroquinolones, most prescribed antibiotic to treat various infections, have increased abdominal aortic aneurysm formation. We aimed to investigate the relation of the development of abdominal aortic aneurysm and the duration of ciprofloxacin use. METHODS: Male Sprague-Dawley rats were divided into 2 groups to administer saline to the control groups and CaCl2 to the aneurysm groups. These groups were then divided into 3 subgroups: intraperitoneal saline, ciprofloxacin for 2 weeks, and ciprofloxacin for 4 weeks. At the end of 4 weeks, the diameter of abdominal aorta was determined by ultrasonography and animals were sacrificed to obtain abdominal aorta specimens. Elastic fiber fracture, tunica media layer thickness, and aortic tissue damage were evaluated histologically. RESULTS: Aortic diameter of control-saline (2.15 mm ± 0.06), control-2 weeks (2.25 mm ± 0.06), and control-4 weeks (3.31 mm ± 0.09) ciprofloxacin groups was significantly different (P .05). CONCLUSION: The study showed that ciprofloxacin caused injury in the aortic wall but not a significant change in the thickness of the aortic tunica media layer. The duration of ciprofloxacin use was important in the development of aneurysm and aneurysm severity.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; CARDIAC & CARDIOVASCULAR SYSTEMS; Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine